Digital Comic Strip as an Information Media on the Impact of Sleep Call - Fauzi, Ahmad Nurzaeni; Wantoro; Melati (International Journal of Research and Applied Technology (INJURATECH), 2025)
Sleep call is a phone or video call activity between two people, usually a couple, that takes place when they are about to sleep. It is not uncommon for sleep calls to be carried out from night until both of them wake up the next morning. This phenomenon, although it has a positive impact on maintaining emotional closeness in the couple's relationship, can also cause various negative impacts such as disturbed sleep patterns, fatigue, and decreased productivity. This design aims to create an effective information media in conveying messages about the impact of sleep calls through comic strip media. Comic strips were chosen as a medium because of their ability to convey messages visually and narratively that are easy to understand and attractive to the target audience, the majority of whom are teenagers to young adults. An informative comic strip can increase audience awareness about the impact of sleep calls and encourage audiences to reconsider habits for good health